Repatriation of a patient with COVID-19 contributed to the importation of an emerging carbapenemase producer. (December 2021) - Moser, Aline I.; Campos-Madueno, Edgar I.; Sendi, Parham; Perreten, Vincent; Keller, Peter M.; Ramette, Alban; Endimiani, Andrea
Highlights: We report a SARS-CoV-2 VOC Delta infection associated with gut colonisation with an OXA-484-producing Escherichia coli. OXA-484 is an OXA-48-like carbapenemase reported only in the UK and Germany. The bla OXA-484 gene shared the same plasmid as bla OXA-181 (51.5 kb, IncX3). bla OXA-484 was carried by a ST410 E. coli that differed from those carrying bla OXA-181. The COVID-19 crisis can contribute to the worldwide spread of emerging carbapenemase producers. ABSTRACT: Objectives: Patients hospitalised abroad can become colonised with multidrug-resistant bacteria and import them to their home countries. In this study, we characterised an OXA-484 carbapenemase-producing Escherichia coli strain from a Swiss patient infected by SARS-CoV-2 and repatriated from India. Methods: At admission to Switzerland (April 2021), the patient undertook a nasopharyngeal swab to search for SARS-CoV-2 and a rectal swab to detect multidrug-resistant bacteria. Both SARS-CoV-2 and E. coli isolates were whole-genome sequenced and analysed for phylogenetic relatedness. Results: The patient was infected with the SARS-CoV-2 B.1.617.2 lineage (VOC Delta), a lineage that began to be reported across Switzerland at that time. He was also colonised with a sequence type 410 (ST410) E. coli strain (L3452210II) producing OXA-484, a single amino acid variant of OXA-181. The bla OXA-484 gene was carried by a 51.5 kb IncX3 plasmid identical to those described in bla OXA-181 -harbouring ST410 E. coli strains. Core genome analysis showed that L3452210II was identical (ΔSNV ≤23) to two ST410 OXA-484 producers recently reported in Qatar and Germany, but differed from other ST410 OXA-181 producers reported worldwide. Conclusion: The patient was infected by an emerging SARS-CoV-2 variant and also imported an E. coli producing OXA-484, an OXA-48-like carbapenemase not yet reported in Switzerland. The genetic background of L3452210II indicated that bla OXA-484 shared the same plasmid as bla OXA-181, but its bacterial host differed from most of the pandemic OXA-181-producing ST410 strains reported previously. This case description underlines that the COVID-19 crisis can contribute to the worldwide spread of emerging carbapenemase producers.